2021
DOI: 10.1155/2021/9930686
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasound Biomicroscopy Diagnosis Analysis and Fine Care of Anterior Segment Injury of Traumatic Anterior Chamber Based on Intelligent Virtual Reality Technology

Abstract: The front part of the eye is exposed to the surface of the body, making it susceptible to injury. Blunt eye injuries often destroy the tissue structure in the anterior part of the eye. Often there is detachment of the iris root, separation of the ciliary body, the angle of retraction of the chamber, and complete dislocation or subluxation of the lens. Ordinary ocular ultrasound can penetrate into opaque tissue, but because of its low resolution, it can only show its outline, which is still very small for docto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Therefore, Li and others believe that due to the limitations of detection methods, it is impossible to carry out accurate morphological quantitative examination and functional measurement of myopia macular retina in clinic. With the gradual development of imaging technology, optical coherence tomography angiography (OCTA) began to be applied in clinic and achieved ideal results [5]. Rahmati and others believed that the equivalent spherical lens in the mild myopia group, moderate myopia group, high myopia group, and ultrahigh myopia group showed a gradual decreasing trend, while the axial length showed a gradual increasing trend.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, Li and others believe that due to the limitations of detection methods, it is impossible to carry out accurate morphological quantitative examination and functional measurement of myopia macular retina in clinic. With the gradual development of imaging technology, optical coherence tomography angiography (OCTA) began to be applied in clinic and achieved ideal results [5]. Rahmati and others believed that the equivalent spherical lens in the mild myopia group, moderate myopia group, high myopia group, and ultrahigh myopia group showed a gradual decreasing trend, while the axial length showed a gradual increasing trend.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through statistical analysis of the ultrasound biomicroscopy biometric values, the VR-technology-based ultrasound biomicroscope performed better than traditional B-scan ultrasound. 25 This study was not explicit in describing and explaining the mechanism of VR implementation in the biomicroscope, possibly because of its emphasis on patient care and outcome.…”
Section: Other Diseases or Conditionsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%